Geostatistics and exploratory factor analysis for special representation of soil chemical attributes in coffee growing - Almeida, Leandro da Silva; Guimarães, Ednaldo Carvalho (Coffee Science - ISSN 1984-3909, 2016)
objective of this study was to evaluate the spatial dependence on chemical soil attributes by means of the geostatistical association and multivariate analysis (exploratory factor analysis), aiming to understand the behavior of the attributes in the soil, thus being able to contribute to the planning of fertilization, seeking greater productivity and sustainability of coffee growing. The research was carried in a grid of 63 sampling points, mounted on a Coffea arabica L. plantation in the cerrado region. Initially was held exploratory factor analysis that generated four factors that together accounted for 97.05% of the total variation of the data. In the geostatistical analysis it was found that the factors 1 and 3 showed spatial dependence, for which the data were interpolated by ordinary kriging (geostatistical). Already the factors 2 and 4 showed pure nugget effect (spatial independence) which held data interpolation by the inverse square of the distance method (classical statistics). The factors 1 and 3 strongly represent the acidity of soil fertility and the soil organic matter. Factors 2 and 4 represent the relationship between the attributes of the ground. The results showed that the use of multivariate techniques in combination with geostatistics can contribute to the coffee crop management in the Cerrado region.